- Profitability, Leverage, and Stock Prices: The Moderating Role of ESG Disclosure: - - Adinda Oktaviya; Acep Komara (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This research is conducted to analyze how profitability and leverage influence stock prices, with Environmental, Social, and Governance (ESG) disclosure positioned as a moderating variable. Using a purposive selection approach with 33 samples, the study focuses on businesses in the basic materials industry that were listed on the Indonesia Stock Exchange in 2024. The data was analyzed using Moderated Regression Analysis (MRA) and multiple linear regression using IBM SPSS Statistics. The findings demonstrate that stock prices are positively and statistically significantly impacted by profitability as determined by ROA. Conversely, the DER, a proxy for leverage, doesn't seem to have much of an impact. Additionally, while it has no effect on the relationship between leverage and stock prices, ESG disclosure strengthens the relationship between profitability and stock prices. These results indicate that investors care more about profitability and sustainability than about capital structure. Therefore, combining ESG practices with financial performance is important for increasing the value of a company and making it more appealing to investors.